Channel assignment and congestion control in multi-radio multi-channel wireless mesh networks - Musaddiq, Arslan (2015)
Wireless Mesh Network (WMN) has been growing rapidly due to its low cost and selforganizing feature. Capacity is one of the most important design goals for WMN. Overall network capacity can be improved by using the Multi-Radios with Multi-Channels (MRMC). IEEE 8021.11a protocol provides 12 non-overlapping channels. In an MR-MC system, the fundamental research problem is the assignment of limited number of frequency channels to the respective radio interfaces. The ultimate objective of this channel assignment (CA) strategy is to reduce the overall network interference and link congestion. If nearby nodes operate on the same frequency channel, they can interfere with each other and produce congestion in the logical links. The MR-MC can provide more coverage area due to multi-hop forwarding and can offer more capacity by simultaneously operating on multiple radios. In this study, a Joint Channel Assignment and Congestion Control (JCACC) scheme for MR-MC WMN has been proposed. The proposed method is based on node queue length information which as-signs the frequency channels based on queue threshold level that indicates the congestion status of the link. OMNET++ simulation tool and graph theory concept have been used to model the network. The algorithm does not allow the node to switch to the channels in which non-intended nodes are operating. JCACC schedules the channel selection mechanism and keeps record of previously congested channel to avoid assigning the same channel again. The simulation based experiment shows the CA for WMN in a quick, efficient and effective manner. The proposed JCACC mechanism provides a more sophisticated solution with 25.16% reduction in round-trip time (RTT) and 24.1% improvement in throughput as compared to previously proposed Distributed Congestion Aware Channel Assignment (DCACA) algorithm.